Nr2e1 Deficiency Augments Palmitate-Induced Oxidative Stress in Beta Cells. (16th November 2015) - Shi, Xiaoli; Deng, Haohua; Dai, Zhe; Xu, Yancheng; Xiong, Xiaokan; Ma, Pei; Cheng, Jing
Abstract : Nuclear receptor subfamily 2 group E member 1 (Nr2e1) has been regarded as an essential regulator of the growth of neural stem cells. However, its function elsewhere is unknown. In the present study, we generated Nr2e1 knockdown MIN6 cells and studied whether Nr2e1 knockdown affected basal beta cell functions such as proliferation, cell death, and insulin secretion. We showed that knockdown of Nr2e1 in MIN6 cells resulted in increased sensitivity to lipotoxicity, decreased proliferation, a partial G0/G1 cell-cycle arrest, and higher rates of apoptosis. Moreover, Nr2e1 deficiency exaggerates palmitate-induced impairment in insulin secretion. At the molecular level, Nr2e1 deficiency augments palmitate-induced oxidative stress. Nr2e1 deficiency also resulted in decreases in antioxidant enzymes and expression level of Nrf2. Together, this study indicated a potential protective effect of Nr2e1 on beta cells, which may serve as a target for the development of novel therapies for diabetes.